Limited Impact of Human Cytomegalovirus Infection in African Infants on Vaccine-Specific Responses Following Diphtheria-Tetanus-Pertussis and Measles Vaccination - Cox, Momodou; Adetifa, Jane U.; Noho-Konteh, Fatou; Njie-Jobe, Jainaba; Sanyang, Lady C.; Drammeh, Abdoulie; Plebanski, Magdalena; Whittle, Hilton C.; Rowland-Jones, Sarah L.; Robertson, Iain; Flanagan, Katie L. (Frontiers in Immunology, 2020)
Human cytomegalovirus (HCMV) infection has a profound effect on the human immune system, causing massive clonal expansion of CD8, and to a lesser extend CD4 T cells. The few human trials that have explored the effect of HCMV infection on responses to vaccination are conflicting, with some studies suggesting no effect whilst others suggest decreased or increased immune responses. Recent studies indicate substantial differences in overall immune system reactivity to vaccines based on age and sex, particularly cellular immunity. 225 nine-month old Gambian infants were immunized with diphtheria-tetanus-whole cell pertussis and/or measles vaccines. HCMV infection status was determined by the presence of CMV DNA by PCR of urine samples prior to vaccination. The effect of HCMV infection on either protective antibody immunity or vaccine-specific and overall cellular immune responses 4 weeks post-vaccination was determined, further stratified by sex. Tetanus toxoid-specific antibody responses were significantly lower in HCMV+ infants compared to their HCMV- counterparts, while pertussis, diphtheria and measles antibody responses were generally comparable between the groups. Responses to general T cell stimulation with anti-CD3/anti-CD28 as well as antigen-specific cytokine responses to purified protein derivative (PPD) were broadly suppressed in infants infected with HCMV but, perhaps surprisingly, there was only a minimal impact on antigen-specific cellular responses to vaccine antigens. There was evidence for subtle sex differences in the effects of HCMV infection, in keeping with the emerging evidence suggesting sex differences in homeostatic immunity and in responses to vaccines. This study reassuringly suggests that the high rates of HCMV infection in low income settings have little clinically significant impact on antibody and cellular responses to early life vaccines, while confirming the importance of sex stratification in such studies.